Faktor-Faktor Yang Mempengaruhi Tingkat Pendapatan Nelayan Desa Galo-Galo Kabupaten Pulau Morotai Kecematan Morotai Selatan - Ardin Umar; Nurhikma Sibua; Jusni - (Jurnal Ilmiah Wahana Pendidikan, 2020)
The people of the village of Galo-Galo, South Morotai Sub-district, Morotai Island Regency are inhabited as fishermen. The title of this research is the factors that influence the level of income of the fishermen in the village of Galo-Galo, South Morotai District, Morotai Island Regency. This type of research used in this study is quantitative research, using primary data and secondary data. Primary data were obtained from questionnaires which were distributed to fishermen and secondary data were obtained from related institutions. Data management is used with the Excel program and entered into the SPSS version 19, with multiple linear analysis methods. The results of the research began the method of multiple linear analysis showed that the age variable has a positive effect on fishermen's income, fuel has a positive effect on fishermen's income, season has a negative effect on fishermen's income and mileage has a positive effect on the income of fishermen in the village of Galo-Galo